2023
DOI: 10.1088/2053-1591/acc82e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MXene, graphene nanoplatelet and multi-walled carbon nanotube on mechanical properties, swelling and flammability behaviour of hybrid sisal/glass fibre reinforced epoxy laminate composites

Abstract: The research work aims to utilize one of the cheapest and most abundantly available natural fibre, sisal fibre, to fabricate a hybrid nanocomposite possessing high performance efficiency. Glass fibre (GFC), sisal fibre (SFC) and hybrid glass/sisal fibre reinforced epoxy laminate composites (HFC) were prepared and subsequently, three of the most promising nano-fillers, MXene (HFCMXN), Graphene nanoplatelet (HFCGNP) and Multi-walled carbon nanotube (HFCCNT), were added into the hybrid composite. The fabricated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…On the contrary, it yielded even lower levels of CO and CO 2 compared to pure EVA. This suggested that oxygen (O 2 ) likely reacted with the combustion and decomposition of EVA, converting it into other substances such as ethers and carbonyl compounds under the kinetic catalysis of e-MXene and silver nanoclusters [23]. Further detailed analysis and demonstration will be provided in the subsequent experimental results.…”
Section: Combustion Performance Evaluation Of Eva Compositesmentioning
confidence: 94%
See 1 more Smart Citation
“…On the contrary, it yielded even lower levels of CO and CO 2 compared to pure EVA. This suggested that oxygen (O 2 ) likely reacted with the combustion and decomposition of EVA, converting it into other substances such as ethers and carbonyl compounds under the kinetic catalysis of e-MXene and silver nanoclusters [23]. Further detailed analysis and demonstration will be provided in the subsequent experimental results.…”
Section: Combustion Performance Evaluation Of Eva Compositesmentioning
confidence: 94%
“…The etched MXene exhibited an accordion-like appearance due to Al layer etching, indicating removal of most Al by hydrogen chloride (HCI) and LiF. Ultrasonic separation then stripped the multi-layer MXene into a few layers (e-MXene) [23]. In figure 2(c), e-MXene showed significantly reduced thickness and irregular outer contour, suggesting random and unstable breaking during ultrasonic stripping [16].…”
Section: Structure Morphology and Thermal Stability Of E-mxene@agmentioning
confidence: 99%